Mortality at one year after transcatheter aortic valve replacement – Relation of age and comorbidities. (December 2022) - Strange, Jarl E.; Fosbøl, Emil L.; Sindet-Pedersen, Caroline; Havers-Borgersen, Eva; Køber, Lars; Gislason, Gunnar H.; Olesen, Jonas B.
Abstract: Background: Of patients undergoing transcatheter aortic valve replacement (TAVR), 80–90 % are at extreme, high, or intermediate risk. Patient selection considering futile outcomes in these groups is difficult as significant comorbidity burden is common. Thus, we examined 1-year mortality after TAVR according to age and comorbidities. Methods: Between 2008 and 2021 all Danish TAVR-patients were included. From a multivariate Cox-regression model, significant characteristics associated with 1-year all-cause mortality were identified. The study population was divided into four groups according to number of significant comorbidities present at baseline: Low (0 comorbidities), mild (1 comorbidity), moderate (2 comorbidities), and high (3 or more comorbidities). The 1-year risk of all-cause mortality with 95 % confidence intervals (CI) was estimated by each group. Results: In total, 7, 104 patients underwent TAVR. Significant covariates associated with 1-year all-cause mortality were chronic kidney disease, heart failure, chronic obstructive pulmonary disease, peripheral artery disease, and age ≥ 85 years. The four baseline groups comprised low (n = 2, 666), mild (n = 2, 814), moderate (n = 1, 246), and high comorbidity burden (n = 378). The 1-year risk of all-cause mortality was 5.5 % (95 %CI: 4.6–6.4 %) in the low baseline comorbidity burden group. Conversely, the 1-year risk of all-cause mortality was 25.0 % (95 %CI: 20.4–29.3 %) in the high baseline burden group. Conclusions: In a national sample of TAVR patients, readily available information on age and comorbidities, can be used to identify a high-risk group with 25 % 1-year mortality. This provides physicians and patients with an easy-to-understand view on 1-year prognosis after TAVR and may complement patient selection for improved long-term outcomes.